Pengataa, ToKaili Customary Spatial Planning: A record of tropical settlements in Central Sulawesi, Indonesia - Sirajuddin, Zaenal; Fitriaty , Puteri; Shen , Zhenjiang (Forestry Faculty, Universitas Hasanuddin, 2022)
Indonesia has experienced multiple disasters induced by several active tectonic faults that cause earthquakes. Central Sulawesi, one of Indonesia's Province, has an active fault known as the Palu-Koro fault. This fault periodically causes disasters (i.e. earthquakes, tsunamis, liquefaction, and landslides). The co-occurrence of these four disasters is locally termed Nalodo. ToKaili – the native tribe that inhabited Central Sulawesi Province – has faced these hazards for generations and formulated local wisdom to minimise their impacts. This local wisdom is called Pengataa. Pengataa serves as a guideline for environmental management, such as determining the location of settlements in consideration of hazards and the environmental equilibrium. This study explores the customary spatial planning (Pengataa) of ToKaili in responding to natural disasters according to disaster records evidence, including the 2018 Palu disaster. This study uses a qualitative method and finds the role of Pengataa in organising ToKaili settlements to minimise the impact of disasters that are free from the effects of Nalodo. This study conveys that customary spatial planning of ToKaili is worthy of considering in the planning of residential areas, especially in relation to natural disasters.